1996
DOI: 10.1177/0148607196020004287
|View full text |Cite
|
Sign up to set email alerts
|

Selenoprotein P in Patients on Home Parenteral Nutrition

Abstract: The positive correlations between selenoprotein P and eGSHPX and plasma selenium indicates that selenoprotein P may be used as a marker of selenium status in selenium-depleted patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Selenium is generally accepted as an essential component of total parenteral nutrition since in its absence deficiency symptoms are observed (198,292), and it has been shown to have a positive effect on immune function in patients on home parenteral nutrition for short-bowel syndrome (285).…”
Section: Selenium In Critical Illnessmentioning
confidence: 99%
“…Selenium is generally accepted as an essential component of total parenteral nutrition since in its absence deficiency symptoms are observed (198,292), and it has been shown to have a positive effect on immune function in patients on home parenteral nutrition for short-bowel syndrome (285).…”
Section: Selenium In Critical Illnessmentioning
confidence: 99%
“…Its concentration in plasma re¯ects the selenium status in healthy subjects (Marchaluk et al, 1995;Persson-Moschos et al, 1995a;Hill et al, 1996) as well as in patients with low selenium status (Persson-Moschos et al, 1995b;Rannem et al, 1996). Selenoprotein P is a selenium-rich protein, which contains up to ten selenocysteine residues per polypeptide chain, compared to one selenocysteine residue in other characterised selenoproteins.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that the concentration of selenium in body fluids in patients on parenteral nutrition depends on the amount of selenium supplied. Thirty-eight patients who had been on parenteral nutrition with no addition of selenium for 3 -216 months had a mean plasma concentration about half of that measured in healthy subjects [29]. Eighty-nine percent of the patients had SeP values lower than mean -2 SD of the reference material, and the lowest value observed was only 3% of the reference value.…”
Section: Sep During Depletion Of Selenium Statusmentioning
confidence: 89%
“…Later, preliminary data from a radioimmunoassay using polyclonal antibodies against human SeP was reported [10]. This assay was then further optimized [26] and employed in different studies [27][28][29][30][31][32][33]. The lowest level of SeP possible to detect thus far was 0.05 arbitrary units, which corresponds to approximately 3% of the normal mean value for plasma SeP.…”
Section: Analysis Of Sepmentioning
confidence: 99%
See 1 more Smart Citation